Preserved expressive language as a phenotypic determinant of Mosaic Angelman Syndrome. Issue 9 (10th August 2019) - Carson, Robert P.; Bird, Lynne; Childers, Anna K.; Wheeler, Ferrin; Duis, Jessica
Abstract: Background: Angelman Syndrome (AS) is a neurodevelopmental disorder with core features of intellectual disability, speech impairment, movement disorders, and a unique behavioral profile. Typically, AS results from absent maternal expression of UBE3A, but some individuals have imprinting defects in a portion of their cells. These individuals are mosaic for normal and defective UBE3A expression, resulting in mosaic AS (mAS) with a partial loss of gene expression. Methods: This study aims to contrast the mAS phenotype to that of AS. Clinical characteristics of mAS were obtained from a parental survey of 22 mAS patients and from the Angelman Natural History study. These were contrasted with those of AS using historical data. Results: Developmental delay was present in nearly all mAS patients, whereas the core features of AS were reported in less than 40%. While language and ability to manage activities of daily living were markedly improved over that expected in AS, mAS patients demonstrated a high incidence of behavioral challenges. Conclusion: Clinical work‐up of an individual with developmental delay, hyperactivity, anxiety, and an uncharacteristically happy demeanor should prompt methylation studies to rule out mAS. We expand the phenotypic spectrum of AS to include features that overlap with Prader‐Willi such as hyperphagia. Abstract : Angelman Syndrome (AS) is a neurodevelopmental disorder that typically results from absence of maternal expression of UBE3A, but some individuals are mosaic for normal and defective UBE3A expression, resulting in mosaic AS (mAS) with only a partial loss of gene expression. This study aims to contrast the mAS phenotype to that of AS, and these data suggest that while mAS presents with a milder phenotype than AS, significant challenges, primarily behavioral, remain. We encourage specialists to consider mAS if they encounter an uncharacteristically happy, anxious, and delayed child, even if the child is verbal and does not have epilepsy.